2018
DOI: 10.1186/s12872-018-0863-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of aortic dilation in patients with coarctation of the aorta: evaluation with dual-source computed tomography

Abstract: BackgroundCoarctation of aorta (CoA) may progressively develop aortic dilation at other site of the aorta and can lead to fatal aortic diseases. We aimed to evaluate the occurrence of aortic dilation and related predictors in patients with CoA using dual-source computed tomography (DSCT).MethodsFifty-three patients with CoA identified by DSCT were retrospectively reviewed. Aortic diameters were measured at six different levels and standardized as z-scores based on the square root of body surface area. Coarctat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
1
16
3
2
Order By: Relevance
“…This is contrary to the study by Zhao et al. (17), which documented concomitant aortic dilatation and collateral circulation in patients with severe aortic coarctation. This discrepancy may result from a well-developed compensatory mechanism in our group of participants with significant aortic stenosis, including smooth muscle proliferation and increased aortic wall thickness (23).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is contrary to the study by Zhao et al. (17), which documented concomitant aortic dilatation and collateral circulation in patients with severe aortic coarctation. This discrepancy may result from a well-developed compensatory mechanism in our group of participants with significant aortic stenosis, including smooth muscle proliferation and increased aortic wall thickness (23).…”
Section: Discussioncontrasting
confidence: 99%
“…The CT-based study by Zhao et al. (17) involved a larger population; however, in contrast to our study, they did not perform an evaluation of clinical symptoms. Another limitation was unsuccessful contact with 2 (6%) patients during the follow-up, which meant that we could not evaluate the clinical symptoms in those individuals.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…BAV is often concomitant with aortic coarctation (CoA)12 and aortic wall complications are frequent in adults with CoA,13 whereas those with progressive course of the disease may also develop aortic dilation and be at risk of aneurysm and aortic dissection. Recent studies have shown that ascending and post-CoA aortic diameters or dilations are linked to the degree of CoA severity14 and that, in a CoA population, patients with BAV were more likely to have moderate or severe ascending aorta (AAo) dilation compared with those with a trileaflet valve 15. While BAV-aortopathy is likely a reflection of BAV morphotype rather than CoA or its physiological effects,16 questions remain about changes in aortic growth in BAV+CoA patients compared with isolated BAV.…”
Section: Introductionmentioning
confidence: 99%